Production and Characterization of Natural Acid-Base Indicator of Kendi Belang and Kendi Bukacu for School Chemistry Experiment - Fatihah, Wahyu; Zidny, Robby (Department of Chemical Education Faculty of Teacher Training and Education Universitas Su, 2023)
The use of litmus paper seems wastefull and less environmentally friendly because it is only used once. For schlools that have difficulty getting litmus paper it can be a practicum obstacle to determine the acidity of the sample. In order to anticipate this problem, indicator paper was made using extracts of the telang flower (Clitoria ternatea) and the kencana ungu flower (Ruellia simplex) plant extracts. The purpose of the study was to observe the color changes that occurred in acid-base paper indicator namely KENDI BELANG (Kertas Indikator Bunga Telang) and KENDI BUKACU (Kertas Indikator Bunga Kencana Ungu) samples for a certain period of time. Other physical changes such as color, odor, flexibility and paper fibers were also observed. The research used an experimental method for 30 days. Research using experimental method for 30 days. The telang flowers and the kencana ungu are obtained from the environment around the house and then extracted. Whatman filter paper was macerated in plant extracts of telang flower (Clitoria ternatea) and purple golden flower (Ruellia simplex), with the addition of aquades and 70% alcohol as solvent. KENDI BELANG using 70% alcohol solvent produces the best quality indicator paper, because there is no change in color and other physical changes during observation. While less optimal result was found on KENDI BUKACU using distilled water, because the indicator paper produces an unpleasant odor, slightly stiff, and there was a color gradations in some samples of acids and bases.